PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP ROA PADA PERUSAHAAN SEKTOR FARMASI YANG TERDAFTAR DI BEI PRIODE 2009- 2013 - Ridho Gilang Adiko (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2017)
Capital market is an indicator of economic progress of a country and support the economic development of the country concerned. Various role of capital market in a country that is as facility to interaction between buyer and seller to measure efficiency of company operation. One of the analytical tools in measuring the effectiveness of companies to generate profit is Return On Assets (ROA). This study aims to examine the factors of Current Ratio (CR) and Total Asset Turnover (TATO) to Return On Assets (ROA) on pharmaceutical sector companies listed on the Indonesia Stock Exchange period 2009 - 2013.              This study uses the entire population of pharmaceutical companies listed on the Indonesia Stock Exchange in 2009 until 2013 as many as 10 companies. Sampling was done by purposive sampling technique. With the sampling method, the samples used in this study as many as 4 companies. The analysis technique used in this research is multiple linear regression analysis technique to test the effect of 5% comparison rate and use t-statistic to test partial regression coefficient.            Regression equation obtained is ROA = - 0,098 + 0,059 CR + 0,036 TATO. This value states if the independent variable is considered 0, then the value of Return On Assets is equal to - 0,098. Variable Current Ratio has the value of regression coefficient is 0,059. The value of this positive coefficient shows that every increase of Current Ratio 1%, then the value of Return On Assets will experience an increase of 0.059. Vice versa, if each decrease of Current Ratio by 1%, then the Return On Assets will decrease by 0.059 as well. Variable Total Asset Turnover has the value of regression coefficient is 0,036. This positive coefficient value indicates that every increase of Total Asset Turnover 1%, then the value of Return On Assets will increase by 0,036 and vice versa, if each decrease of Total Asset Turnover by 1%, then Return On Assets will decrease equal to 0,036 also.            The available and used data have been qualified for multiple linear regression models. From this research, the conclusion is as follows: Current Ratio variable has an effect on and significant to ROA, and variable of Total Asset Turnover has no effect and significant to ROA. This is evidenced by the magnitude of t arithmetic for the CR table is 8.328> 1.725 and the significant value of CR is 0,000 <0.05 which denotes CR affect the ROA. Then the magnitude of t arithmetic for the TATO table is 1.559 <1.725 and the significant value of TATO is 0.137> 0.05 indicating TATO has no effect on ROA. Judging from the F test, as F calculated 46,668> 31,410 indicating Current Ratio and Total Asset Turnover influence on Return On Asset. In addition, the significant value of 0.000 <0.05 indicating Current Ratio and Total Asset Turnover affect the Return On Asset.            The amount of coefficient of determination (adjusted R square) is equal to 0.828 which means ROA is influenced by independent variables, it shows the contribution / influence of CR and TATO to ROA of 0.828 or 82.8% so that other variables outside the ratio (external factor) Return On Assets on Pharmaceutical Sector Companies Listed on the BEI is 17.2%.Keywords: Current Ratio (CR), Total Asset Turnover (TATO), Return On Assets (ROA)